Synthesis and Biological Activity of Brassinosteroid Analogues with a Nitrogen-Containing Side Chain - Diachkov, Mikhail V; Ferrer, Karoll; Oklestkova, Jana; Rarova, Lucie; Bazgier, Vaclav; Kvasnica, Miroslav (International journal of molecular sciences, 2020)
Brassinosteroids are a class of plant hormones that regulate a broad range of physiological processes such as plant growth, development and immunity, including the suppression of biotic and abiotic stresses. In this paper, we report the synthesis of new brassinosteroid analogues with a nitrogen-containing side chain and their biological activity on Arabidopis thaliana. Based on molecular docking experiments, two groups of brassinosteroid analogues were prepared with short and long side chains in order to study the impact of side chain length on plants. The derivatives with a short side chain were prepared with amide, amine and ammonium functional groups. The derivatives with a long side chain were synthesized using amide and ammonium functional groups. A total of 25 new brassinosteroid analogues were prepared. All 25 compounds were tested in an Arabidopsis root sensitivity bioassay and cytotoxicity screening. The synthesized substances showed no significant inhibitory activity compared to natural 24-epibrassinolide. In contrast, in low concentration, several compounds (8a, 8b, 8e, 16e, 22a and 22e) showed interesting growth-promoting activity. The cytotoxicity assay showed no toxicity of the prepared compounds on cancer and normal cell lines.
Keywords: Molecular Structure; Arabidopsis; molekulární struktura; Chemistry Techniques, Synthetic; vývoj rostlin; cytotoxicity; nitrogen-containing steroid; plant bioassay; Nitrogen; Plant Development; organic synthesis; dusík; techniky syntetické chemie; brassinosteroid; brassinosteroidy; Brassinosteroids